UPAYA MENINGKATKAN KEMAMPUAN MEMBEDAKAN SIFAT KOLIGATIF LARUTAN ELEKTROLIT DAN LARUTAN NONELEKTROLIT DENGAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE MAKE A MATCH PADA SISWA KELAS XII-MIA-1 DI SMA NEGERI 1 PEUDAWA ACEH TIMUR - Maryati Maryati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2021)
This research is a Classroom Action Research (CAR). This research was conducted in class XII-MIA-1 SMA Negeri 1 Peudawa, East Aceh Regency in the odd semester of the 2020/2021 academic year. The students who were used as objects of research were 27 students of class XII-MIA-1 consisting of 11 male students and 16 female students. The subjects that are the focus of the research are Chemistry subjects, the subject of discussion is to distinguish the colligative properties of electrolyte solutions and nonelectrolyte solutions. The application of the make a match type of cooperative learning model aims to improve student learning outcomes in class XII-MIA-1 SMA Negeri 1 Peudawa, East Aceh Regency. This research was conducted in two cycles. Based on the results of the study, the following conclusions were obtained: 1) There were differences in student learning outcomes in the material to distinguish colligative properties of electrolyte solutions and non-electrolyte solutions before and after using the Make–A Match type of Cooperative Learning learning model, 2) There was an increase in student learning outcomes in differentiating materials. colligative properties of electrolyte solutions and nonelectrolyte solutions using the Make-A Match type of cooperative learning model, namely in the pre-cycle there were only 33.3% of students who completed with an average score of 58.2, then in the first cycle it increased to 62.9% students who completed with an average score of 69.8, and in the second cycle increased back to 88.9% of students who completed with an average value of 75.3, and 3) In the first cycle there has been an increase in students who are complete in distinguishing characteristics. colligative electrolyte solution and nonelectrolyte solution but still need improvement in the teaching and learning process using mo del learning Cooperative Learning type Make–A Match. Furthermore, in the second cycle, the student's learning mastery target has been achieved.Keywords: electrolyte and nonelectrolyte solution, make a match model.